Análise da influência dos parâmetros do microfresamento na liga de latão C230 modificado por extrusão de canal angular - Zorzete, Arthur Rubini (2023)
Due to the advance of companies and their growing demand for micro-sized components, micro-machining processes have stood out in the machining area. These processes characterization is not only refer conventional machining process reduction, because the cutting thickness and the material grain size are compatible the cutting tool edge radius, that results in the scale effect. This effect describes changes in the cutting behavior and in the material properties when the machining is performed in micro scale. For minimize this effect it pursue for alternatives for modify the material structure. This way, in this work was utilize the angular chanel extrusion process (ECAP), in order to reduce grain size and analyze whether such reduction would interfere with burr formation in micromilling, roughness and microhardness. The results showed that ECAP modified the material microstructure, lengthening grains and work hardening them, resulting in the increase hardness. How much the burr size, the channels with 0.05 mm cutting depth and 3 µm/tooth feed got the best results. On the other hand, channels obtained with 0.05 mm cutting depth and 0.02 µm/tooth and 10 µm/tooth feed rates of showed the best roughness results. Regarding on the burr size, the samples that was processed by ECAP had inferior performance is compared the samples without ECAP, but it was possible to utilize a feed per tooth value larger for the modified samples.